Epistemic trust towards teacher questionnaire: Development and preliminary validation - Alex Desatnik; Maxim Yakubovskiy; Sergei Tarasov; Peter Fonagy (PLoS ONE, 2025)
Epistemic trust (ET) is a well-established concept in evolutionary developmental psychology. It refers to the trust recipients place in their informants, which in turn makes them more attentive, thoughtful, and engaged in processing and acquiring information. This concept plays a key role in educational contexts, as leveraging this innate mechanism could help teachers to improve learning outcomes, including those beyond the classroom. This paper describes the development and validation of a new self-report measure, the Epistemic Trust Towards Teacher (ETT) scale, designed to assess the unique role of ET in education. The study focuses on the development of the scale, its factor structure, and construct validity. The study participants were 224 middle and high school students aged 11–15 (58.5% female). Confirmatory factor analysis supported a three-factor structure with good model fit (χ²/df = 1.9; CFI = 0.970; TLI = 0.965; RMSEA = 0.062), consisting of Trust (ETT_T), Mistrust (ETT_M), and Generalisation (ETT_G) subscales. Reliability was acceptable to excellent across the three subscales (Cronbach’s α = .75–.88). The factors showed good discriminant validity and aligned with theoretical expectations. The ETT scales correlated in theoretically consistent ways with established measures of teacher-student relationship quality, working alliance, non-verbal immediacy, and student motivation. Overall, this study provides preliminary support for the ETT as a relevant and psychometrically sound instrument in the field of educational psychology. Further research is required to investigate the ETT’s performance across a wider age range and diverse educational settings.